Heterozygous missense variant in EIF6 gene: A novel form of Shwachman–Diamond syndrome?. Issue 9 (13th July 2020) - Koh, Ai Ling; Bonnard, Carine; Lim, Jiin Ying; Liew, Woei Kang; Thoon, Koh Cheng; Thomas, Terrence; Ali, Nur Ain Binte; Ng, Alvin Yu Jin; Tohari, Sumanty; Phua, Kong Boo; Venkatesh, Byrappa; Reversade, Bruno; et al.
Abstract: Shwachman–Diamond syndrome (SDS) is a rare multisystem ribosomal biogenesis disorder characterized by exocrine pancreatic insufficiency, hematologic abnormalities and bony abnormalities. About 90% of patients have biallelic mutations in SBDS gene. Three additional genes— EFL1, DNAJC21 and SRP54 have been reported in association with a SDS phenotype. However, the cause remains unknown for ~10% of patients. Herein, we report a 6‐year‐old Chinese boy, who presented in the neonatal period with pancytopenia, liver transaminitis with hepatosplenomegaly and developmental delay, and subsequently developed pancreatic insufficiency complicated by malabsorption and poor growth. Exome sequencing identified a novel de novo heterozygous variant in EIF6 (c.182G>T, p.Arg61Leu). EIF6 protein inhibits ribosomal maturation and is removed in the late steps of ribosomal maturation by SBDS and EFL1 protein. Given the interaction of EIF6 with SBDS and EFL1, we postulate heterozygous variants in EIF6 as a novel cause of Shwachman–Diamond‐like phenotype. We compared the phenotype of our patient with those in patients with mutation in SBDS, EFL1, DNAJC21, and SRP54 genes to support this association. Identification of more cases of this novel phenotype would strengthen the association with the genetic etiology.